URBAN FARMING: EFFORTS TO IMPROVE FOOD SECURITY FOR URBAN COMMUNITIES - Yudi Garnida (Sean Institute, 2022)
Food insecurity is becoming an increasingly urgent problem in the modern world, particularly in urban areas, which frequently have a high degree of reliance on the food supply provided by outside sources. Urban farming as a concept has the potential to be an appealing solution to this problem and could be one way to address it. The purpose of this research is to examine the viability of urban farming as a strategy for enhancing the food security of people who live in cities. This investigation takes a qualitative approach and makes use of descriptive research tools. The findings of the study indicate that urban farming involves the growing of a variety of plants, including those used for food and ornamentation, as well as the raising of fish, chickens, and bees. The benefits of urban farming include the ability to satiate the need for high-quality food, the generation of new employment opportunities, the promotion of a higher intake of freshly harvested fruits and vegetables, the enhancement of both physical and mental health, and the establishment of a wholesome natural environment. Increasing the food security of families can be accomplished through urban farming in many different forms, such as living stalls and fish growing in buckets, as just two examples.